Role Changing of Governance Subject in Unit Community Reconstruction -- Study on Community composition of Xinhua Printing No.2 Factory of Hunan Province - Bi, Wei; He, Zidong (2020 International Conference on Urban Engineering and Management Science (ICUEMS), 2020)
It is well known that unit community is the product of "unit urbanism" in the early days of new China. On the one hand, it met the needs of urban development of the country at that time, and on the other hand, it also met the management needs of government departments. As an enterprise unit with production as the core, Xinhua printing No.2 factory's community composition was a "reproduction space of labor force" in the early stage, later with the demand of upper management, it became more and more complete and the unit community even became a "small society", in which people's daily life diet, daily communication, cultural activities all could be satisfied. However, these functions have been gradually changed over time, some commercial functions were disappeared due to the booming of outside industry, as well as traditional cultural function also gradually abandoned due to change in the daily activities and diversification. Though environment of unit community still remain comfortable because of past suitability, using quality of community residents do not improved accordingly. Therefore, as boundaries of the unit community open up and become more integrated with the surrounding environment, how to respond to surrounding residents' increasingly diversified demand for material space under community function change has become one of the common problems faced by unit and community commonly.